Manajemen Sumber Daya Manusia: Tren dan Tantangan di Era Digital - Radeswandri (Lembaga Anotero Scientific, 2024)
This study explores the significance, trends, and challenges of Human Resource Management (HRM) in the digital era. Through a comprehensive literature review and qualitative analysis, including interviews and case studies, the research highlights the substantial benefits of digitalization in HRM, such as increased operational efficiency, data-driven decision-making, and enhanced employee engagement and retention. However, it also identifies critical challenges, including resistance to change, a lack of digital skills, and data security concerns. The findings emphasize the importance of strategic approaches to overcoming these challenges, such as continuous digital skill development programs, fostering an organizational culture that supports innovation and flexibility, and investing in advanced data security technologies. The study concludes that successful digital transformation in HRM requires ongoing monitoring and evaluation, collaboration with experienced technology providers, and strong leadership support. Implementing these strategies can optimize HRM practices, improve operational efficiency, and contribute to achieving strategic goals and competitive advantage in the global market.